INTERACTIVE METADISCOURSE MARKERS IN INDONESIAN EFL STUDENTS’ ACADEMIC WRITING - Pasaribu, Arsen Nahum; Pasaribu, Tiara K; Sinambela, Erika; Manullang, Vitri Rosalina (English Review: Journal of English Education, 2022)
The research on metadiscourse markers investigation in academic texts has grown very rapidly in the last decade. However, research on interactive metadiscourse markers on EFL students' academic writing is still relatively underexplored. Therefore, this study aims to reveal how the competence of EFL students in the use of interactive metadiscourse in academic writing by comparing two groups of students with different grades, third-semester students and fifth-semester students. The research design is a combination of quantitative and qualitative methods. A total of 40 students were participating in this research and divided into two groups. Each group consists of 20 students. They were assigned to write a minimum-250-word essay about the importance of English mastery in the disrupted era of 4.0. Around 818 interactive markers were identified in the student’s essay texts. The results reveal that the use of interactive discourse markers in the students' writing was considered still low in quantity. The transition markers were the most dominant found in the text, followed by frame markers, code gloss, endophoric markers, and evidential respectively. Moreover, the students in the fifth semester perform slightly better than their third-semester counterparts at using the interactive metadiscourse markers. However, most of the students in both groups still encountered difficulties to employ the interactive markers in their writing. The lack of practice and the student's native language practice might have contributed to the low quality of the student's writing.